RISK FACTORS FOR CHRONIC NONCOMMUNICABLE DISEASES IN THE MINISTRY OF EMERGENCY SITUATIONS PERSONNEL - E.YU. SHKATOVA; I.A. KOBILYATSKAYA (Паёми Сино, 2021)
Objective: To establish risk factors (RFs) for the development of noncommunicable diseases (NCDs) among the Ministry of Emergency Situations (MChS) personnel.